Histogram Equalization Software to Enhance Digital Image by Visual Studio 2010 - Asmaidi Asmaidi; S. Fahmi Junanda; Teti Novia Dewi (Jurnal Inotera, 2018)
Digital image (image) is another term for picture, as one of the multimedia components plays a very important role as a form of visual information. Image processing is a process that involves a lot of visual perception. A grayscale image is an image that has only one channel value in each pixel, in other words the values ​​of Red, Green, Blue are used to indicate the intensity level. Pixel (Picture Elements) is the value of each matrix entry in the bitmap. This pixel is affected by the number of colors that can be displayed. Image improvement is one of the simplest and most attractive methods in digital image processing. Basically, the idea behind image improvement techniques is to bring out obscured details or just to highlight certain interesting features. Histogram Equalization/Histogram leveling is a histogram smoothing process, where the distribution of gray level values ​​of an image is made evenly.